Preliminary and Pharmacological Profile of Melia azedarach L.: An Overview - Deepika Sharma and Yash Paul (Journal of Applied Pharmaceutical Science, 2013)
The tree Melia azedarach (Family: Meliaceae) is known locally as bakain or drek (Hindi), Persian lilac or China tree (English), and Fleurs lilas (French). In South America is commonly known as “paraiso” or paradise, and in the US as Indian lilac or white cedar. The whole plant or its specific parts (leaves, stem, and roots) are known to have medicinal properties and have a long history of use by indigenous and tribal people in India. Melia azedarach is used as an ayurvedic medicine in India and Unani medicine in Arab countries as an antioxidative, analgesic, anti-Inflammatory, insecticidal, rodenticidal, antidiarrhoeal, deobstruent, diuretic, antidiabetic, cathartic, emetic, antirheumatic and antihypertensive. It is highly nutritious having a calorific value at 5100 kcal/kg. Also, it is used to manufacture agricultural implements, furniture, plywood, boxes, poles, tool handles and fuel wood. It is widely planted as a shade tree in coffee and abaca (Musa textilis) plantations. It is a well-known ornamental tree. The present review is therefore, an effort to give a detailed survey of the literature on its botanical details, phytochemical reports, pharmacological studies and its therapeutic importance.
Keywords: Bakain, Drek, Botanical details, Phytochemical reports, Pharmacological studies.